Clinical trial of L‐Carnitine and valproic acid in spinal muscular atrophy type I. Issue 2 (18th September 2017) - Krosschell, Kristin J.; Kissel, John T.; Townsend, Elise L.; Simeone, Sarah D.; Zhang, Ren Zhe; Reyna, Sandra P.; Crawford, Thomas O.; Schroth, Mary K.; Acsadi, Gyula; Kishnani, Priya S.; Von Kleist‐Retzow, Jürgen‐Christoph; Hero, Barbara; et al.
ABSTRACT: Introduction: The aim of this study was to determine the safety and therapeutic potential ofL ‐carnitine and valproic acid (VPA) in infants with spinal muscular atrophy (SMA). Methods: Our investigation was an open‐label phase 2 multicenter trial ofL ‐carnitine and VPA in infants with SMA type I with retrospective comparison to an untreated, matched cohort. Primary outcomes were: safety and adverse events; secondary outcomes were survival, time to death/>16 hours/day of ventilator support; motor outcomes; and maximum ulnar compound motor action potential amplitude. Results: A total of 245 AEs were observed in 35 of the 37 treated subjects (95%). Respiratory events accounted for 49% of all adverse events, resulting in 14 deaths. Survival was not significantly different between treated and untreated cohorts. Discussion: This trial provides evidence that, in infants with SMA type I, L ‐carnitine/VPA is ineffective at altering survival. The substantial proportion of infants reaching end‐points within 6 months of enrollment underscores the urgent need for pre‐symptomatic treatment in SMA type I. Muscle Nerve 57 : 193–199, 2018